Gambaran Status Gizi pada Anak Down Syndrome di Samarinda - Sarita, Nadia Rahma; Danial; Muhyi, Annisa (Jurnal Medika : Karya Ilmiah Kesehatan, 2023)
Down Syndrome (DS) is a congenital disorder that occurs during fetal development caused by non-disjunction chromosome 21 or trisomy 21. One of the health problems faced by DS children is nutritional status. This study aims to describe the nutritional status of children with Down syndrome in Samarinda. This study used a descriptive observational design with a cross-sectional approach which was carried out in February 2023 at Persatuan Orang Tua dengan Anak Down Syndrome (POTADS). The primary data were obtained through written interviews with the child's companion and measurements of length or height and weight in DS children. Samples were collected with accidental sampling method and obtained 30 samples. The results showed that the age of DS children with good nutritional status was mostly found in the group aged ≥ 1 – 3 years (16.7%). The gender of DS children with good nutritional status was mostly found in males (36.7%). The mother's education level of DS children with good nutritional status was mostly found in high school (23.3%). It was found that the most family income level of DS children with good nutritional status was ≤ UMK (33.3%). Keywords: Down Syndrome, children, nutritional status.